2021
DOI: 10.4103/ojo.ojo_27_21
|View full text |Cite
|
Sign up to set email alerts
|

Case report of central retinal artery occlusion following bee sting injury: A possible link?

Abstract: We report the case of a 54-year-old male who presented with complaints of decreased vision in the left eye (LE). He gave a history of multiple bee stings following which he had an episode of allergic anaphylaxis to the face and neck region for which he was admitted and treated with steroids. On examination, he was found to have LE central retinal artery occlusion (CRAO) which was the cause of his reduced vision. This is the first report of a bee sting venom as a cause for CRAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this patient, blurred vision and visual loss in left eye were reported 2 and 48 h, respectively, after being stung, which were consistent with the fundus fluorescein angiography examination showing CRAO with one cilioretinal artery sparing. Recently, one study reported the first case of CRAO following multiple bee stings ( 9 ). The exact pathogenesis of CRAO in this case is not clear, because the systemic workup including blood investigations, carotid Doppler, and echocardiography was within normal range at 1 week following the incidence, which might be attributed to steroid-induced resolution of allergic and toxic reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this patient, blurred vision and visual loss in left eye were reported 2 and 48 h, respectively, after being stung, which were consistent with the fundus fluorescein angiography examination showing CRAO with one cilioretinal artery sparing. Recently, one study reported the first case of CRAO following multiple bee stings ( 9 ). The exact pathogenesis of CRAO in this case is not clear, because the systemic workup including blood investigations, carotid Doppler, and echocardiography was within normal range at 1 week following the incidence, which might be attributed to steroid-induced resolution of allergic and toxic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation caused by bee stings, such as keratopathy and endophthalmitis, has been well-reported ( 5 – 8 ). Recently, Pujari et al described a patient with CRAO after bee sting; this patient was treated with systemic steroids and his systemic workup was normal at 1 week following the incidence, the exact pathogenesis of CRAO in this case is not clear ( 9 ). In this study, we present another case of visual loss caused by CRAO after bee sting, which was accompanied with hypersensitivity, hypercoagulable state, myocardial damage, and hepatic damage.…”
Section: Introductionmentioning
confidence: 92%